2023
DOI: 10.1002/art.42535
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 1 Enhances Transport and Golgi Organization Protein 1 Expression to Promote Procollagen Export From the Endoplasmic Reticulum in Systemic Sclerosis Contributing to Fibrosis

Abstract: ObjectiveTANGO1 (Transport ANd Golgi Organization protein 1) is a protein that regulates the export of procollagen from the endoplasmic reticulum and has a role in the organization of exit sites for general protein export. What regulates the expression of TANGO1, and its role in fibrosis, is poorly understood, and has never been studied in systemic sclerosis (SSc). We undertook these studies to determine the role for TANGO1 in SSc fibrosis.MethodsSSc (n=15) and healthy (n=12) primary fibroblast lung cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…TGF-β has been implicated in IBD as lower active levels are observed (76), due to increased expression of TGF-β inhibitor Smad7 in the intestinal mucosa (77, 78), prompting us to investigate the effect of TGF-β on mucin-2 trafficking. Consistent with previous research (36, 79), TGF-β induced expression of TANGO1. The effect of inhibiting TGF-β on TANGO1 has not been reported previously, however, the decreased expression is in line as an antagonistic response to TGF-β stimulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…TGF-β has been implicated in IBD as lower active levels are observed (76), due to increased expression of TGF-β inhibitor Smad7 in the intestinal mucosa (77, 78), prompting us to investigate the effect of TGF-β on mucin-2 trafficking. Consistent with previous research (36, 79), TGF-β induced expression of TANGO1. The effect of inhibiting TGF-β on TANGO1 has not been reported previously, however, the decreased expression is in line as an antagonistic response to TGF-β stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Generally, post-transcriptional and post-translational modifications play an important role in the formation of large COPII vesicles (92). Recently, it was shown that TANGO1 expression was dependent on inflammasome activation of caspase-1, as well as signaling from IL-1 and TGF-β (79). Elucidating the post-transcriptional mechanism of TANGO1, possibly mediated by TGF-β, could identify therapeutic targets for IBD and fibrosis.…”
Section: Discussionmentioning
confidence: 99%